2022
DOI: 10.1007/s11914-022-00746-7
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Muscle Mass Loss in Critical Illness: the Role of Nutrition and Exercise

Abstract: Purpose of Review Impaired recovery following an intensive care unit (ICU) admission is thought related to muscle wasting. Nutrition and physical activity are considered potential avenues to attenuate muscle wasting. The aim of this review was to present evidence for these interventions in attenuating muscle loss or improving strength and function. Recent Findings Randomised controlled trials on the impact of nutrition or physical activity interventions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…To date, the evidence base for nutrition recommendations, particularly those including muscle wasting are limited. A recent review examining randomized controlled trials of nutrition interventions in critical illness that included an outcome of muscle mass, function, or strength found no nutrition intervention had an effect on strength or function, and the effect on muscle mass was conflicting [54]. This is likely a reflection of the complexity of nutrition as an intervention, the short-term nature of the interventions and the heterogeneity present both in the critical illness patient population and in the patient response to nutrition.…”
Section: Testing Novel Strategies With Standardised Meaningful Outcom...mentioning
confidence: 99%
“…To date, the evidence base for nutrition recommendations, particularly those including muscle wasting are limited. A recent review examining randomized controlled trials of nutrition interventions in critical illness that included an outcome of muscle mass, function, or strength found no nutrition intervention had an effect on strength or function, and the effect on muscle mass was conflicting [54]. This is likely a reflection of the complexity of nutrition as an intervention, the short-term nature of the interventions and the heterogeneity present both in the critical illness patient population and in the patient response to nutrition.…”
Section: Testing Novel Strategies With Standardised Meaningful Outcom...mentioning
confidence: 99%
“…In healthy overweight subjects, a 20% calorie restriction over 12–14 weeks led to a 3% reduction in appendicular lean body mass [ 32 ]. As muscle catabolism is accelerated during critical illness, any additional muscle loss from prolonged underfeeding may have a detrimental impact on muscle structure, function and recovery [ 33 ].…”
Section: The Clinical Relevance Of Energy Balancementioning
confidence: 99%
“…This narrative review found that no nutrition intervention has shown an effect on strength and function. There was some indication that higher levels of early physical activity resulted in improved strength and function [8]. Although not included in this review, a prospectively planned sub-analysis of the Early Parenteral Nutrition Completing Enteral Nutrition in Adult Critically Ill trial – found patients had less weakness with late parental nutrition compared with early parental nutrition (absolute difference −9%, 95% confidence interval [CI] −16 to −1; P = 0·030) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Two recent reviews summarized the literature within the acute (defined as within ICU for the purpose of this review) [8]; and sub-acute period of critical illness (defined as post-ICU for the purpose of this review) [9]. Within the acute period, the first review presented the evidence for physical activity and nutrition in attenuating muscle loss or improving strength and function – across varied ICU patient cohort although most required mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%